(untitled) (Research, Society and Development, 2023)
The present study comparatively evaluated the cutting capacity and resistance of two instrumentation sequences considering the difference in weight after preparation of the root canal simulated in transparent acrylic resin blocks with a standardized curvature angle of 45°. Resources have been subjected to a maximum of ten sterilization and use cycles. The blocks were weighed on a maximum precision digital scale before and after preparation, followed by verification of weight loss regarding the cutting capacity of the instruments through the interference of multiple uses and autoclaving, since the resistance analysis can be verified through the amount of blocks used for each protocol, up to a maximum limit of ten blocks per group, except for the occurrence of fracture. It can be concluded that the TruNatomy® system was more effective in terms of resistance, considering its performance in the ten intended blocks, unlike the Proglider® plus WaveOne Gold Primary® protocol, where there was a fracture on the fifth use. As for cutting capacity, the WaveOne Gold Primary® instrument (mean of 4 blocks=3.4629g) presented a slight advantage over TruNatomy® (mean of 4 blocks=3.4506g), but without statistical significance.